SYNTHESIS OF 1-(3,4-BIS(BENZYLOXY)PHENYL)-2-(4(SUBSTITUTEDSULFONYL)PIPERAZIN- 1-YL)ETHANONES: MOLECULAR DOCKING AND ANTIBACTERIAL PROPERTIES - PAWANJEET KAUR; DURGARAO KANTHETI; SN MURTHY BODDAPATI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The aim of the study was to prepare a series of piperazine sulfonamide analogs (7a-l) and to perform in silico and in vitro antibacterial studies to determine their antibacterial activity. Methods: All the synthesized sulfonamides are characterized by different spectroscopic techniques. Further, the antibacterial screening results revealed that the synthesized sulfonamides exhibit good antibacterial activities. Results: Among the synthesized compounds, 7c and 7f displayed noteworthy antibacterial activity. The piperazine sulfonamide 7c exhibited superior inhibition of Enterobacter aerogenes and Bacillus subtilis pathogens with minimum inhibitory concentration (MIC) values of 81±0.78 and 49±1.02 μg/mL, respectively. The molecule 7f is most effective against E. aerogenes and B. subtilis with consecutive MIC’s of 86±0.58 μg/mL and 67±0.76 μg/mL. Moreover, the molecular docking studies were performed to comprehend the compounds binding interactions. Using in silico studies, the designed molecules were effectively screened as Escherichia coli deoxyribonucleic acid gyrase enzyme (PDB: 4BAE) inhibitors. The molecular docking studies for all the synthesized piperazine sulfonamide analogs (7a-l) were carried out using Maestro 11.2 and geometry optimized by Macro model program v9.1 (GLIDE, Schrodinger, LLC). In addition, to categorize the ligands accountable for the anti-bacterial activity, the molecular docking simulations were performed with software AutoDock Vina of PyRx and the Discovery studio. The obtained piperazine sulfonamide hybrids 7c and 7f gained superior molecular docking scores of −5.62 and −5.70, respectively. The structure activity relationships of the target sulfonamides were established. Conclusion: The in vitro antibacterial screening outcomes revealed that the molecules 7f and 7c showed potent anti-bacterial activity and good binding energy in docking analysis.